6(4-c)=5(c-2)

Simple and best practice solution for 6(4-c)=5(c-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4-c)=5(c-2) equation:


Simplifying
6(4 + -1c) = 5(c + -2)
(4 * 6 + -1c * 6) = 5(c + -2)
(24 + -6c) = 5(c + -2)

Reorder the terms:
24 + -6c = 5(-2 + c)
24 + -6c = (-2 * 5 + c * 5)
24 + -6c = (-10 + 5c)

Solving
24 + -6c = -10 + 5c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5c' to each side of the equation.
24 + -6c + -5c = -10 + 5c + -5c

Combine like terms: -6c + -5c = -11c
24 + -11c = -10 + 5c + -5c

Combine like terms: 5c + -5c = 0
24 + -11c = -10 + 0
24 + -11c = -10

Add '-24' to each side of the equation.
24 + -24 + -11c = -10 + -24

Combine like terms: 24 + -24 = 0
0 + -11c = -10 + -24
-11c = -10 + -24

Combine like terms: -10 + -24 = -34
-11c = -34

Divide each side by '-11'.
c = 3.090909091

Simplifying
c = 3.090909091

See similar equations:

| 3(y-1)-(3y-1)=2y-1-(2y+1) | | 4x+-21x=91 | | x+5/3=2x-5/6 | | f(x)=x^3-7x^2+7x+15 | | w+(2w-4)+w+(2w-4)=46 | | 0.25-0.5=0.05 | | 7x^2-42=35x | | 3t+9=33 | | 9-9=12x+11x | | 8.2x-5=0 | | .50x+.4x=18 | | -60+2.5x=0 | | 16+t=-182 | | 15-4x=7-5x | | .10x+.25(x+4)+.05*5(x+4)=3.20 | | x+2y=zforx | | 3+4x+2x=12+4x-3x | | 4(1+6m)-8=-124 | | 3x+45=8x-220 | | 36=-9t | | 0=12m | | 21x^2+2x-.09=0 | | cos(x)=-05 | | (2xy)(3x^2y)= | | -84x^2+91x-7=0 | | 4y=8+3x | | (x^2-5)(5x)(-.25)= | | (n-2)180=108n | | 7(14a+7w)8(7a+9w)= | | (4+n)+(3n-7)i=8-2i | | x+4x+3=17 | | 2x+7y=27 |

Equations solver categories